A comparison between Air-Q® intubating laryngeal mask airway and C-MAC® video laryngoscope for intubation in simulated difficult intubation patients with cervical collar - Sumpat, Donna (2018)
Background: Special airway devices are useful adjunct during difficult airway situation. The aim of this study was to compare between Air-Q® intubating laryngeal mask airway (ILMA) and C-MAC® video laryngoscope in term of effectiveness of intubation, intubation time, haemodynamic changes and complication post intubation in stimulated using cervical collar. Methods: 80 patients, age 18-60 years, ASA I-II, with no features of difficult intubation who were scheduled for elective surgery under general anaesthesia were randomized into two groups: Group Air-Q (n=40) and Group C-MAC (n=40). After successful induction with IV fentanyl (1-1.5 mcg/kg), IV propofol (1.5-2 mcg/kg) and IV rocuronium (1 mg/kg), cervical collar was applied to all patients. Group Air-Q was inserted with Air-Q® ILMA followed with blind intubation through it. Group C-MAC was intubated using C-MAC® video laryngoscope. The ease of intubation, intubation time, haemodynamic changes and complications were recorded. Results: C-MAC® video laryngoscope showed higher successful rate of first attempt intubation than Air-Q® ILMA (100% vs 55%, P=0.001). Requirement of optimization however was significantly more in Air-Q® ILMA than C-MAC® video laryngoscope (37.5% vs 5.0%, P=0.001). Mean duration of intubation was shorter in C-MAC® than Air-Q® ILMA (57.8±14.4s vs 164.6±58.0s, P=0.001). There was no significance difference in haemodynamic parameters and complication in post intubation. Conclusion: Intubation with C-MAC® video laryngoscope was better in success rate and shorter in intubation time than blind intubation with Air-Q® ILMA in simulated difficult airway patients. However, the complication post intubation was comparable.